Voltammetry of chromium(VI) at the liquid|liquid interface - O'Mahony, A.; Scanlon, M.; Berduque, A.; Beni, V.; Arrigan, Damien; Faggi, E.; Bencini, A. (Elsevier Inc., 2005)
The voltammetry of hexavalent chromium (ammonium dichromate) at the interface between two immiscible electrolyte solutions is reported. Detection of Cr(VI) by ion transfer voltammetry is possible by use of an organic phase ionophore, which facilitates the transfer of Cr(VI) from the aqueous into the organic phase. The ionophore was the penta protonated form of polyamine macrocycle 2,5,8,11,14-pentaaza[15]-16,29-phenanthrolinophane (NeoTT). Cyclic voltammetry showed an increase of the peak current on increasing the concentration of Cr(VI). Square wave voltammetry with background subtraction was employed for low level concentration detection. The lowest concentration detected was 0.25 parts per million of Cr(VI).